Whole-genome-based characterization of invasive Haemophilus influenzae isolates from a pre- and post-vaccine era in Portugal - Gonzalez Diaz, Aida (2018)
Introduction: Haemophilus influenzae (Hi) is responsible for severe invasive infections in both adults and children. Since the introduction in the year 2000 of the Hib vaccine, the incidence of disease has substantially declined, even though it doesn’t protect against non-typeable Hi (NTHi) isolates. Although not all NTHi are pathogenic, these are known to possess important virulence factors to promote colonization and host cells interactions, ultimately leading to disease. The application of WGS technology allows the uncovering of Hi population structure, including novel insights into its genomic features. Aims: This study aims to fully characterize, by WGS, Hi isolates from a pre- and post-vaccine era, from 1992 to 2015, in Portugal. Materials and Methods: Ninety invasive Hi isolates from the Portuguese NIH collection were selected for WGS. More than half were NTHi (63.3%) and 32.2% of the strains belong to a pre-vaccine era. Genomes were assembled and both sequence type (ST) and serotype were determined by PCR and confirmed in silico. A core-single nucleotide polymorphism-based phylogenetic tree was reconstructed to analyze overall genomic diversity between strains. Strains were further characterized by identifying the presence and genetic profile of genes related to antibiotic resistance and virulence factors, namely genes involved in adherence, host immune evasion, iron acquisition and lipooligosaccharides (LOS). Results: Preliminary results show high ST heterogeneity among NTHi, contrasting with the homogeneity of ST for Hib strains (all ST6, except one). Core-SNP-based analysis revealed that all strains were distinguishable by more than 140,000 single nucleotide variant sites, with a highest genetic diversity observed between NTHi (overall ~35,000 nucleotide differences). Interestingly, although all Hib segregated together, the ST282 Hib strain possessed a distinct genome profile, diverging by ~17,200 nucleotide differences from ST6, while these overall diverged between them by ~2,480. Differential presence of important virulence factors was observed among strains, namely for hia/hsf, hmw1/hmw2, hap and iga, with distinct genomic profiles observed between strains, requiring in-depth analysis. Curiously, 90% of NTHi had the lgtA LOS-coding gene which was absent in all Hib. Additionally, five genes coding for other LOS were found to be simultaneously present or absent among NTHi strains, most belonging to a post-vaccine era, indicating a potential cluster of circulating strains. Conclusions: Overall, we expect that the integrative analysis of all Hi isolates will strengthen the characterization of the genomic features in pre- and post-vaccine era, ultimately contributing to the understanding of the scenario of strains circulating in Portugal throughout more than 20 years.